Determining social factors related to pesticide poisoning among rice farmers in Colombia (2016)
Objective Large quantities of pesticides are used in rice crops. The aim of this study is to characterize how farmers are exposed to pesticides and subsequent poisoning. Materials and Methods A multilevel (individual and community) multi-method study, which included ethnographic and survey methods, as well as measurement of pesticides in water and human samples, was performed. Results The production process is described and the main risk factors are presented. Pesticides are considered the greatest danger at work and at their homes. Workers have poor working conditions and are not protected by the system of occupational risks. Azinphos-methyl, endosulfan, ?-BHC, bromophos-methyl, bromophos-ethyl and 2,4-DDT were found in water samples. The survey included 381 workers with mild (12.86%), moderate (67.98%) and severe (5.51%) poisonings respectively. Severe cases presented lower levels of education, lower levels of health care access to the contributory regimen of the Colombian social security system and higher incidence of cardiovascular disease, diabetes, herpes or other viral infections. Conclusion There are precarious working conditions that favor exposure to pesticides correlated to the exclusion of farmers from the occupational risk system, to poverty and to poor education. It is urgent to include these workers to the system of occupational risk system and to improve their living conditions, thus reducing unsafe practices when handling pesticides. © 2016, Universidad Nacional de Colombia. All rights reserved.